Determination of Electrolyte Transport Properties with a Multi-Reference-Electrode Cell. Issue 6 (8th June 2021) - Rabette, C.; Tekaya, I.; Farkhondeh, M.; Fleutot, B.; Delacourt, C.
Abstract : Fast charging is one of the main challenges of electric vehicles, partly due to electrolyte transport limitations across porous electrodes in Li-ion cells. The determination of electrolyte transport properties is crucial for modeling fast charging and adjust cell design accordingly. In this work, diffusion coefficient and cation transference number for a 1 M LiPF6 in ethylene carbonate/diethyl carbonate mixture (1:1 in weight) are determined using a multireference electrode electrochemical cell (four herein). It is an extension of the work by Farkhondeh et al. [J. Phys. Chem. C 2017, 121, 8, 4112–4129] that was based on two reference electrodes. Long galvanostatic pulses allow for building up concentration gradients across the cell (restricted diffusion), which are subsequently let to relax under open circuit. The multiple voltages (three herein) measured between the four reference electrodes are simultaneously analyzed with four different procedures that involve a combination of analytic methods and nonlinear regression of the data with a numerical model. The parameter mean values and 95%-confidence intervals are evaluated using Student t -distribution and the bootstrap method. Values reported by combining all methods together are: D = 2.62 × 10 − 10 ± 2.29 % m 2 s − 1, t + 0 = 0.204 ± 12.25 % at 25 °C.